PEMANFAATAN AMPAS KEDELAI PADA PEMBUATAN BROWNIES “GLUTEN FREE” UBI JALAR UNGU DAN UJI KELAYAKANNYA - Arnida Mustafa; Ela Elliyana (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
Soybean pulp is a byproduct of tofu processing and soy milk. The nutrients contained in soybean dregs are still significantly high, especially protein and fiber. So far, processing of soybean pulp into food is still limited. Tuber has many benefits for the body, and has a high nutritional content and can be used as a food substitution. One of the tubers that can be processed as a substitute is purple sweet potato. The natural fiber of oligosaccharides or anti-nutrition substances stored in purple sweet potatoes is a valuable commodity for processed food products, such as brownies. This study aims to determine the quality, physicochemical and organoleptic properties produced by brownies. The study was organised using a completely randomized design (CRD) with a comparison treatment of soybean pulp paste and purple sweet potato paste including (1) 60%, 50%, 40% and (2) 40%, 50%, 60%. Each treatment was repeated three times. The study was conducted at the Pangkep State Agricultural Polytechnic Biochemistry Laboratory (PPNP) of South Sulawesi. The results of the study obtained the best quality of brownies on physicochemical properties in treatment D (A3B3), by the concentration of 40% soybean paste paste and 60% purple sweet potato paste for water content (25.76%), ash (1.01%), fat (14.56%), carbohydrate (43.32%), and protein (18.95%). The best growth power test for the physical quality of brownies is in treatment D (A3B3) with a concentration of 40% soybean pulp paste treatment and 60% purple sweet potato paste (6.4 cm). The best panelist's level of preference test was in treatment D (A3B3) with a concentration of 40% soybean paste paste treatment and purple sweet potato paste 60% for color (4.28%), aroma (3.95%), flavor (4.47% ) and texture (4.42%).